The hybrid prince - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2026)
"Umber followed the clawmarks (if that's what they were), finding one every few trees until he reached what seemed to be the halfway point of the beach. To his left, the island curved away out of sight, and to his right, a stretch of craggy rocks trailed into the ocean and cut off the view beyond... And here, at the midpoint, the clawmarks changed. Umber felt a chill run through his scales. There were words carved into the trees. Not safe here, the jagged letters read. Keep going."--